Surveying concepts and primary strategies of action in adolescent mental health - Gonçalves, M. (2013)
According to WHO (2005), barriers to care for the mental health needs of children and adolescents exist in all countries and at all levels. Barriers identified as most important include (among others) financial and geographical inaccessibility and stigma. However, the extent of these barriers is still unclear from the perspective of the adolescents. Moreover, migrants and ethnic minorities may perceive more and stronger barriers. An international research team, from Switzerland, Brazil and Portugal, has developed a project that seeks to answer this question with the study AMHC Access to Mental Health Care, initiated in Switzerland in 2004. A survey on concepts and primary strategies of action in adolescent mental health was developed and conducted among children aged 12-16, including migrants and ethnic minorities. In this paper data from Portugal will be presented. Findings of 106 students (17,9% with migrant background) and 56 caregivers show that stereotypes and stigma continue to be the biggest perceived barriers to the access to mental health care, similarly to those found Switzerland and Brazil. Preventive and intervention strategies in the school setting are therefore discussed.